New Insights into Development of Maternity Hospitals in the Republic of Croatia after World War II: Outpatient Maternity Department in Klanjec, Hrvatsko Zagorje, Croatia - Rajko Fureš; Milan Stanojević; Žana Stanić; Dora Fureš; Vesna Ćosić; Željka Fureš; Sanja Malinac Malojčić; Martin Gredičak; Zlatko Hrgović; Ivana Erceg Ivkošić; Nika Mikelin (Acta Clinica Croatica, 2024)
In the area of today’s Krapina-Zagorje County, after World War II, there were three outpatient maternity departments (OMD) in Krapina, Klanjec and Pregrada, making a considerable step forward in public health improvement. The first and biggest OMD was located in the Klanjec Public Health Center. In parallel with establishment of the maternity hospital (MH) in Zabok, all OMDs throughout today’s Krapina-Zagorje County were closed. The aim of our research was to present the activities of Klanjec OMD (KOMD) and show its impact on perinatal health. Data on KOMD activities were obtained from the Birth Registry. Major obstetric procedures, including delivery by cesarean section, were not performed in KOMD. Based on the above, numerous transports of women in labor and postpartum transports were organized to maternity wards in large centers. The most common cause for transport were transports during childbirth caused by prolonged labor. In conclusion, organization of OMD in the area of today’s Krapina-Zagorje County significantly improved perinatal care in the 1950s. It was followed by gradual closure of OMD which could not meet the newly set spatial, material and personnel demands, along with the establishment of maternity hospitals in general and university hospitals. The trend of perinatal and maternal mortality reduction in the Zagorje region that began with the establishment of inpatient maternity department at the Zabok Hospital continues to this day.